CONTRIBUTIONS TO THE IMPLEMENTATION OF ENVIRONMENTAL MANAGEMENT SYSTEM WITHIN THE ECO TECHNOLOGIC ORGANIZATION - Gheorghe AMZA; Dan DOBROTA (Fiabilitate şi Durabilitate)
This paper presents contributions to the implementation of environmental management system within the eco technologic organization. SME type organization's environmental policies highlights the accomplishment of requirements of ISO 19001 standard, regarding pollution prevention, commitment in accordance to the law and if it is documented and can provide a framework for setting environmental objectives and targets. The audit may reveal whether it corresponds to the nature, scale and impact that activities, products and services of the organization have on the environment, or if it is implemented, maintained and communicated to all staff. This paper presents mainly the following: elements of environmental planning process, environmental planning process, place of environmental conservation in the general strategy of the organization